Initiating polyketide biosynthesis by on-line methyl esterification - Pengwei Li (Nature Portfolio, 2021)
Aurantinins are polyketides with unusual connectivities and broad antibacterial activity. Here the authors show the biosynthesis of aurantinins, which proceeds via an on-line methyl esterification at the terminus that enables the iterative chain elongations prior to condensation and cyclization.